Successful application of lead isotopes in source apportionment, legal proceedings, remediation and monitoring - Gulson, B.; Korsch, M.; Winchester, W.; Devenish, M.; Hobbs, T.; Main, C.; Smith, G.; Rosman, Kevin; Howearth, Lynette; Nunes, Laurie; Seow, J.; Oxford, C.; et al. (Academic Press, 2012)
In late 2006, the seaside community in Esperance Western Australia was alerted to thousands of native bird species dying. The source of the lead (Pb) was determined by Pb isotopes to derive from the handling of Pb carbonate concentrate through the Port, which began in July 2005. Concern was expressed for the impact of this on the community. Our objectives were to employ Pb isotope ratios to evaluate the source of Pb in environmental samples for use in legal proceedings, and for use in remediation and monitoring. Isotope measurements were undertaken of bird livers, plants, drinking water, soil, harbour sediments, air, bulk ceiling dust, gutter sludge, surface swabs and blood. The unique lead isotopic signature of the contaminating Pb carbonate enabled diagnostic apportionment of lead in samples. Apart from some soil and water samples, the proportion of contaminating Pb was >95% in the environmental samples. Lead isotopes were critical in resolving legal proceedings, are being used in the remediation of premises, were used in monitoring of workers involved in the decontamination of the storage facility, and monitoring transport of the concentrate through another port facility. Air samples show the continued presence of contaminant Pb, more than one year after shipping of concentrate ceased, probably arising from dust resuspension. Brief details of the comprehensive testing and cleanup of the Esperance community are provided along with the role of the Community. Lead isotopic analyses can provide significant benefits to regulatory agencies, interested parties, and the community where the signature is able to be characterised with a high degree of certainty.